Occupational stress and its relationship to the quality of professional life among nurses of the hospital institution “Ain AlAssal“ in El Tarf - Thanti, Hala (Journal of Human Sciences, 2023)
This study aims to measure the relationship This study aims to measure the relationship between work pressure and the quality of professional life among nurses in the Hospital Institution for Neighborhood Health - Ain Al-Assal - in the state of El Tarf, and to achieve the objectives of the study, the researcher adopted the descriptive analytical approach as the most appropriate for psychosocial studies, through the design of a questionnaire directed to the study sample, which numbered (27) nurses in the hospital institution - Ain Al-Assal - and the study reached the following results: There is a statistically significant relationship between work stress and occupational quality of life, there is a correlation between personal work stress and occupational quality of life, there is no correlation between environmental work stress and occupational quality of life, there is a correlation between organizational work stress and occupational quality among nurses.